Update on classification of lymphomas - Robin Sabharwal; Keya Sircar; Shamindra Sengupta; Bhudev Sharma (Wolters Kluwer Medknow Publications, 2013)
Lymphomas constitute approximately 5% of all malignant neoplasms of the head and neck. They are divided into two major subtypes, Hodgkin's lymphomas and non-Hodgkin's lymphomas, depending on the presence or absence of Reed-Sternberg cells. Controversy in the classification of lymphomas dates back to the first attempts to formulate such classifications. Much of this controversy arose from the assumption that there must be a single guiding principle, a "gold standard" for classification. Earlier classifications of lymphomas were based on the morphology, treatment response, and survival and some were based on cell lineage and differentiation. The International Lymphoma Study Group (I.L.S.G.) developed a consensus list of lymphoid neoplasms, which was published in 1994 as the "Revised European-American Classification of Lymphoid Neoplasms" (REAL). The classification was based on the principle that a classification is a list of "real" disease entities, which are defined by a combination of morphology, immunophenotype, genetic features, and clinical features and there cannot be a single "gold standard."